Spatiotemporal Characteristics of Extreme Precipitation and Its Future Trend Analysis in Huaihe River Basin - GUO Wei; YE Wen; ZHU Xuchao; WU Wei; WANG Lu; GAO Huamin; ZHANG Haiming; SHI Shaohui (Renmin Zhujiang)
Amid global warming, water and heat patterns will experience changes on a regional scale, resulting in frequent occurrence of extreme climate events. As a typical extreme climate event, extreme precipitation is more sensitive to climate change. To investigate the extreme precipitation change characteristics in the Huaihe River Basin in history (1961‒2022) and in the future, this paper employs historical observation precipitation data from meteorological stations, CMIP6 model simulations, and atmospheric circulation observation data. Meanwhile, extreme precipitation indices are adopted to quantify extreme precipitation characteristics. It also investigates the change trend of extreme precipitation by Mann-Kendall trend analysis and the climate tendency rate method and analyzes the relationship between extreme precipitation and atmospheric circulation factors based on the wavelet analysis method in the Huaihe River Basin. The results are as follows. (1) Extreme precipitation has generally shown an increasing trend in the past 60 years in the Huaihe River Basin. The increasing trends of R95p and R99p are relatively large with the value of 0.46 mm/a and 0.43 mm/a respectively. (2) Different extreme precipitation indices witness an increasing trend more significant than previous records in the history under the SSP2-4.5 and SSP5-8.5 scenarios from 2023 to 2100. Under the SSP2-4.5 scenarios from 2023 to 2100, the future change trends of extreme precipitation intensity, frequency, and duration are 78.3%, 63.5%, and 350% more than the historical trends in the Huaihe River Basin. Under the SSP5-8.5 scenario during that time period, the future change trends of extreme precipitation intensity, frequency, and duration are 158%, 130%, and 450% more than the historical trends in the Huaihe River Basin. (3) The correlation between extreme precipitation indices and southern oscillation index (SOI) is higher than that of north Atlantic oscillation (NAO). The relationship between extreme precipitation of the same type and atmospheric circulation factors is relatively similar. This study can provide a deep understanding of extreme precipitation changes on a regional scale in the context of global warming, providing references for flood disaster prevention in the Huaihe River Basin in the future.